Internet addiction among secondary school students in Kuala Lumpur - Chew, Kai Qing; Roslan, Samsilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Many researchers have shown that the Internet users are at risk of developing an obsessive dependency or “addiction” towards Internet. A descriptive correlational study was intended to investigate the relationship among time-used online, types of Internet use and Internet addiction among Secondary School students. A total of 431 respondents involved in this study were Secondary School students ranging from 13 to 18 years old living in Kuala Lumpur. The selection of respondents was based on a two-stage cluster sampling method. Instruments that were used were the Demographic Characteristic Sheet, Internet Addiction Test, Types of Internet Use and Tim-used online. An administered Malay version of Internet Addiction Test was used to overcome the language barrier. The pencil and paper test took place in the schools monitored by academic staffs, and was given 45 minutes to fill in. The time-used online, types of Internet use and Internet Addiction were measured using descriptive and correlation methods. The Internet Addiction level among respondents was significantly different between male and female Secondary School students, where male score higher addiction levels than female. Results showed that Internet use such as Social Networking Websites, Chat rooms, gaming Websites and Videos were moderately correlated with Internet Addiction scores. Among Secondary School students in Kuala Lumpur, time-used online and types of Internet use is correlated with Internet Addiction level.